2012
DOI: 10.1038/onc.2012.483
|View full text |Cite
|
Sign up to set email alerts
|

miR-30d, miR-181a and miR-199a-5p cooperatively suppress the endoplasmic reticulum chaperone and signaling regulator GRP78 in cancer

Abstract: GRP78, a major endoplasmic reticulum chaperone and signaling regulator, is commonly overexpressed in cancer. Moreover, induction of GRP78 by a variety of anti-cancer drugs, including histone deacetylase inhibitors, confers chemoresistance to cancer, thereby contributing to tumorigenesis. Thus, therapies aimed at decreasing GRP78 levels, which results in the inhibition of tumor cell proliferation and resensitization of tumor cells to chemotherapeutic drugs may hold promise for cancer treatment. Despite advances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
86
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 53 publications
(75 reference statements)
7
86
0
Order By: Relevance
“…It was reported that increased miR-181a aggravated injury in a mouse stroke model by inhibiting GRP78 protein expression levels, whereas reduced levels of miR-181a were associated with increased GRP78 protein levels and reduced injury (33). In several cancer cell lines, GRP78 was reported to be regulated by miR-199a-5p as well as miR-30d and miR-181a and cooperatively suppressed GRP78-mediated chemoresistance (45). Similarly, Dai et al (5) reported that miR-199a-5p was evaluated during hepatic ER stress and directly regulated the expression of GRP78 in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that increased miR-181a aggravated injury in a mouse stroke model by inhibiting GRP78 protein expression levels, whereas reduced levels of miR-181a were associated with increased GRP78 protein levels and reduced injury (33). In several cancer cell lines, GRP78 was reported to be regulated by miR-199a-5p as well as miR-30d and miR-181a and cooperatively suppressed GRP78-mediated chemoresistance (45). Similarly, Dai et al (5) reported that miR-199a-5p was evaluated during hepatic ER stress and directly regulated the expression of GRP78 in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the implications of upregulation of miR-181a in MPC samples remains unclear. Additionally, Su et al (36) reported that the downregulation of miR-30d and miR-181a in prostate tumors cooperatively suppresses the expression of glucose-regulated protein, 78 kDa (GRP78), a major endoplasmic reticulum chaperone and signaling regulator that is typically overexpressed in cancer (37). Differential expression of GRP78 was not observed in the present study; however, MYH11 was revealed to be another common target of miR-30d and miR-181a, indicating that miR-30d and miR-181a may cooperate to regulate the metastasis of PC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The potential links between the UPR, miR-1291, IRE1 and GPC3 require further clarification. BiP (GRP78), the major ER chaperone and signaling regulator, was shown to be a direct target of miR-30a, miR-181a and miR-199a-5p [78]. These three miRNAs are downregulated in prostate, colon and bladder tumors, and in a number of human cancer cell lines.…”
Section: Upr Mirnasmentioning
confidence: 99%
“…These three miRNAs are downregulated in prostate, colon and bladder tumors, and in a number of human cancer cell lines. Induction of these miRNAs in C42B prostate cancer cells attenuated BiP expression and induced apoptosis [78], meaning these miRNAs may be a part of the apoptotic UPR response. Another study by Dai et al [54] demonstrated that miR-199-5p is induced in hepatocytes during thapsigargin-induced ER stress, and targets BiP mRNA along with ATF6 and IRE1α.…”
Section: Upr Mirnasmentioning
confidence: 99%